Cord Blood Natural Killer Cells Inhibit Sepsis Caused by Feces-Induced Acute Peritonitis via Increasing Endothelium Integrity. (April 2022) - Lan, Jing; Zhang, Hong; Zhao, Hui; Liu, Linghong; Shi, Qing; Li, Dong; Ju, Xiuli
Sepsis is associated with acute peritonitis, which can be induced by lipopolysaccharide exposure and feces. Generally, lipopolysaccharide induces mono-microbial peritonitis, whereas feces cause poly-microbial peritonitis; the latter is a more complicated and closer to the clinical diseases. Although several reports have discussed the mechanism of immune response in peritonitis-induced sepsis, however, the role of natural killer (NK) cells in sepsis, especially the relationship between NK cells and stabilization of the vascular endothelial barrier, is still unclear. Accordingly, in this study, we assessed the roles of NK cells in an acute sepsis model in mice. NK cells were injected via the tail vein into mice with acute sepsis, and nitric oxide (NO), anti-inflammatory cytokine, and angiogenic factors were tested to explore the effects of NK cells on sepsis. The survival rate of septic model mice infused with NK cells was significantly improved compared with the control group. Interestingly, the levels of NO, interleukin-10, and vascular endothelial growth factor (VEGF) decreased in NK cells therapy group. After the injection of NK cells, CD31 positive endothelial cells significantly increased in the kidneys and liver, although the expression of VEGF, ANGPT-1, and ET-1 was downregulated. Consistent with our hypothesis, the transfusion of NK cells into mice with sepsis blocked inflammation and increased endothelium integrity. Overall, these findings suggest that NK cells may block sepsis by modulating the VEGF pathway.